Theoretical Approach of Laser Excited Solids: Exploring the effects of laser excitation on solids (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This  paper  introduce  the basic concepts  of the theoretical  description of laser- induced  structural  changes in  solids. The approaches usedare mainly based on the calculation of the time-dependent potential energysurface and an explicit treatment of electronic degrees of freedom.Key words:  Workforce diversity, disability, old age, human resource management, equal opportunity.